Pengaruh Konflik Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan melalui Stres Kerja sebagai Variabel Intervening di PT. Semen Tonasa Sulawesi Selatan - Muhayminah A.P, Raissa; Sahabuddin, Romansyah; Musa, Muh. Ichwan; Burhanuddin; Natsir, Uhud Darmawan (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of work conflict and work environment on employee performance with work stress as an intervening variable at PT Semen Tonasa. The method used is a quantitative approach with Partial Least Square (PLS) analysis. The results of the study indicate that work conflict has a significant positive effect on work stress, while the work environment has a significant negative effect on work stress. Work conflict does not have a significant effect on employee performance, while the work environment has a significant positive effect. Work stress is also proven to have a significant negative effect on employee performance. In addition, work stress does not mediate the effect of work conflict on performance, but partially mediates the effect of the work environment on performance. These findings emphasize the importance of conflict management, improving the work environment, and stress control to support employee performance.